2009
DOI: 10.1007/s11105-009-0097-0
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of ISSR and RAPD Markers for Study of Genetic Diversity in Shisham (Dalbergia sissoo)

Abstract: Shisham (Dalbergia sissoo) is one of the most preferred timber tree species of South Asia. Two DNAbased molecular marker techniques, intersimple sequence repeat (ISSR) and random amplified polymorphism DNA (RAPD), were compared to study the genetic diversity in this species. A total of 30 polymorphic primers (15 ISSR and 15 random) were used. Amplification of genomic DNA of 22 genotypes, using ISSR analysis, yielded 117 fragments, of which 64 were polymorphic. Number of amplified fragments with ISSR primers ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 19 publications
6
24
1
3
Order By: Relevance
“…This finding is opposite to that reported by Arif et al (2009), who worked with Shisham (D. sisso). Some researchers have shown that ISSR markers are distributed throughout the genome and may be associated with functionally important loci (Penner, 1996;Esselman et al, 1999), while RAPD markers are located in non-coding regions and therefore are selectively neutral (Bachmann, 1997;Landergott et al, 2001 …”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding is opposite to that reported by Arif et al (2009), who worked with Shisham (D. sisso). Some researchers have shown that ISSR markers are distributed throughout the genome and may be associated with functionally important loci (Penner, 1996;Esselman et al, 1999), while RAPD markers are located in non-coding regions and therefore are selectively neutral (Bachmann, 1997;Landergott et al, 2001 …”
Section: Discussioncontrasting
confidence: 99%
“…We found high genetic variability among different genotypes of D. oliveri in the Yok Don National Park. RAPD and ISSR molecular markers have been commonly used in population genetics studies and for detecting clonal diversity in many species (Parsons et al, 1997;Esselman et al, 1999;Li and Ge, 2001;Chen et al, 2006;Gupta et al, 2008;Arif et al, 2009 (Rout et al, 2003). Andrianoelina et al (2006) also quantified and analyzed the genetic variation of D. monticola, using RAPDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies these markers show very close results, for example 85.4% and 85.2% polymorphic fragments, respectively (Liu et al 2008). There are also enough works suggesting that RAPD-PCR exceeds ISSR-PCR by the ability to reveal polymorphism (Venkatachalam et al 2008;Farajpour et al 2011, Lalhruaitluanga & Prasad 2009Arif et al 2009;Gupta et al 2008;Mishra 2009;Xavier et al 2011;Biswas et al 2010). It seems possible that differences in the effectiveness of various marker systems are related to differences in genome structure of species under study, namely to proportion of coding and non-coding sequences within the genome.…”
Section: Discussionmentioning
confidence: 99%
“…ElHady et al (2010) have shown that individual or combined RAPD and ISSR markers can be used effectively to determine genetic relationships among Vigna species. Similarly, both RAPD and ISSR markers have been used in genetic diversity analysis and genotype identification in plants such as banana, betel vine, castor, elephant grass, rice bean, shisham, and tea (Devarumath et al, 2002;Lakshmanan et al, 2007;Muthusamy et al, 2008;Arif et al, 2009;Gajera et al, 2010;de Lima et al, 2011;Patra et al, 2011). Many authors have found that ISSR markers are highly polymorphic and exhibit higher levels of efficiency, reproducibility, and accuracy than those of RAPD markers (Souframanien and Gopalakrishna, 2004;Ghalmi et al, 2010;Ali et al, 2011).…”
Section: Introductionmentioning
confidence: 99%